Complementary Approaches to Assess Phytoplankton Groups and Size Classes on a Long Transect in the Atlantic Ocean - Brotas, Vanda; Tarran, Glen A.; Veloso, Vera; Brewin, Robert J. W.; Woodward, E. Malcolm S.; Airs, Ruth; Beltran, Carolina; Ferreira, Afonso; Groom, Steve B. (Frontiers in Marine Science, 2022)
Phytoplankton biomass, through its proxy, Chlorophyll a, has been assessed at synoptic temporal and spatial scales with satellite remote sensing (RS). Also, RS algorithms to monitor relative size classes abundance are widely used; however, differentiating functional types from RS, as well as the assessment of phytoplankton structure, in terms of carbon, remains a challenge. Hence, the main motivation of this work it to discuss the links between size classes and phytoplankton groups, to foster the capability of assessing phytoplankton community structure and phytoplankton size fractionated carbon budgets. Data on nutrients, photosynthetic pigments concentration and cell numbers per taxa were collected in surface samples along a transect on the Atlantic Ocean, during the 25th Atlantic Meridional Transect cruise between 50o N to 50o S. We compared phytoplankton size classes from two methodological approaches: i) concentration of diagnostic photosynthetic pigments, and assessing the abundance of the three size classes, micro-, nano- and picoplankton, and ii) identifying and enumerating phytoplankton taxa by microscopy or by flow cytometry, converting into carbon, and dividing the community into five size classes, according to their cell carbon content. The distribution of seven functional types on the transect showed the dominance of picoautotrophs in the Atlantic gyres and high biomass of diatoms and autotrophic dinoflagellates in higher northern and southern latitudes, where larger cells constituted the major component of the biomass. Total carbon ranged from 65 to 4 mg carbon m-3, at latitudes 45o S and 27o N, respectively. The pigment and cell carbon approaches gave good consistency for picoplankton and microplankton size classes, but nanoplankton size class was overestimated by the pigment-based approach. The three-component model of Brewin et al. (2010) was fitted to the Chla data and, for the first time, to the carbon data. The general pattern of the model fitted to the carbon was in accordance with the fits to Chla. The ratio of maximum biomass gave reasonable values for Carbon:Chla ratios, with an overall median of 112, with higher values for picoplankton (170) than for combined pico-nanoplankton (36). The approach may be useful for inferring size-fractionated carbon from Earth Observation.